Investigation of microphysical parameterizations of snow and ice in Arctic clouds during M-PACE through model-observation comparisons - Solomon, Amy (author); Morrison, Hugh (author); Persson, Ola (author); Shupe, Matthew (author); Bao, Jian-Wen (author) (Monthly Weather Review, 2009)
In this study the Weather Research Forecast model is used with 1-km horizontal grid spacing to investigate the microphysical properties of Arctic mixed-phase stratocumulus. Intensive measurements taken during the Department of Energy Atmospheric Radiation Measurement Program Mixed-Phase Arctic Cloud Experiment (M-PACE) on the North Slope of Alaska, during 9-12 October 2004, are used to verify the microphysical characteristics of the model’s simulation of mixed-phase clouds (MPCs). A series of one- and two-moment bulk microphysical cloud schemes are tested to identify how the treatment of snow and ice affects the maintenance of cloud liquid water at low temperatures. The baseline two-moment simulation results in realistic liquid water paths and in size distributions of snow reasonably similar to observations. With a one-moment simulation for which the size distribution intercept parameter for snow is fixed at values taken from the two-moment simulation, reasonable snow size distributions are again obtained but the cloud liquid water is reduced because the one-moment scheme couples the number concentration to the mixing ratio. The one-moment scheme with the constant snow intercept parameter set to a value typical of midlatitude frontal clouds results in a substantial underprediction of the liquid water path. In the simulations, the number concentration of small ice crystals is found to be underestimated by an order of magnitude. A sensitivity test with the concentration of ice particles larger than 53 μm increased to the observed value results in underprediction of the liquid water path. If ice (not snow) is the primary driver for the depletion of cloud liquid water, then the results of this study suggest that the feedbacks among ice-snow-cloud liquid water may be misrepresented in the model. OAR Outstanding Scientific Paper Award, National Oceanic and Atmospheric Administration (NOAA), 2011